Denosumab for the treatment of HIV-associated osteoporosis with fractures in a premenopausal woman - E. Marasco; M. Mussa; F. Motta; F. Bobbio-Pallavicini; R. Maserati; C. Montecucco; L. Bogliolo (Reumatismo, 2021)
The prevalence of osteoporosis is about three times greater in people living with HIV than in the general population. Bisphosphonates are the only class of antiresorptive drugs which have proved to be safe and effective in HIV patients. However, bisphosphonates are not recommended in women of childbearing age due to an increased rate of associated neonatal complications. To the best of our knowledge no reports on the use of denosumab in HIV-infected individuals have been published so far. We describe a 38 year-old woman with HIV, osteoporosis and vertebral fractures treated with denosumab, a monoclonal antibody targeting RANKL. After four years of treatment, bone mineral density improved, no new fractures occurred, and neither HIV reactivation nor opportunistic infections were observed. We show that denosumab could be a safe and effective approach for osteoporosis in patients with HIV and could be considered in women of childbearing age.